An Organizing Framework for Translation in Public Health: The Knowledge to Action Framework - Katherine M. Wilson, PhD, MPH, CHES; Teresa J. Brady, PhD; Catherine Lesesne, PhD, MPH (Centers for Disease Control and Prevention, 2011)
A priority for the Centers for Disease Control and Prevention (CDC) is translating scientific knowledge into action to improve the public's health. No area has a more pressing need for translation than the prevention and control of chronic diseases. Staff from CDC's National Center for Chronic Disease Prevention and Health Promotion worked across disciplines and content areas to develop an organizing framework to describe and depict the high-level processes necessary to move from discovery into action through translation of evidence-based programs, practices, or policies. The Knowledge to Action (K2A) Framework identifies 3 phases (research, translation, and institutionalization) and the decision points, interactions, and supporting structures within the phases that are necessary to move knowledge to sustainable action. Evaluation undergirds the entire K2A process. Development of the K2A Framework highlighted the importance of planning for translation, attending to supporting structures, and evaluating the public health impact of our efforts.